# Let f(x) = x^{2} + 3x − 4 and g(x) = x + 5. Find f(x) ⋅ g(x).

We will be using the concept of multiplying two functions to solve this.

## Answer: If (x) = x^{2} + 3x − 4 and g(x) = x + 5, then f(x) ⋅ g(x) = x^{3} + 8x^{2} + 11x - 20.

Let's solve it step by step.

**Explanation:**

Given that, f(x) = x^{2} + 3x − 4 and g(x) = x + 5.

We know that, f(x) ⋅ g(x) = f(x) × g(x)

f(x) ⋅ g(x) = (x^{2} + 3x − 4) × (x + 5)

f(x) ⋅ g(x) = x^{3} + 3x^{2} − 4x + 5x^{2} + 15x - 20

f(x) ⋅ g(x) = x^{3} + 8x^{2} + 11x - 20